Standardization of cross-site biophysical studies of bovine insulin amyloids is challenged by structural polymorphism - Sofie Nyström; Davide Odino; Annalisa Relini; Claudio Canale; Raffaella Parlato; Yari Knelissen; Alessia Lasorsa; Wouter H. Roos; Patrick C.A. van der Wel; Søren V. Hoffmann; Nykola C. Jones; Vincent van Hemelryck; et al. (European Biophysics Journal, 2026)

Can triad forestry reconcile Europe’s biodiversity and forestry strategies? A critical evaluation of forest zoning - Thomas A. Nagel; Mariano Rodríguez-Recio; Tuomas Aakala; Per Angelstam; Admir Avdagić; Zbigniew Borowski; Andrés Bravo-Oviedo; Gediminas Brazaitis; Thomas Campagnaro; Michał Ciach; Milic Curovic; Inken Doerfler; et al. (Ambio, 2025)
Balancing increasing demand for wood products while also maintaining forest biodiversity is a paramount challenge. Europe’s Biodiversity and Forest Strategies for 2030 attempt to address this challenge. Together, they call for strict protection of 10% of land area, including all primary and old growth forests, increasing use of ecological forestry, and less reliance on monocultural plantations. Using data on country wide silvicultural practices and a new database on strict forest reserves across Europe, we assess how triad forest zoning could help meet these goals. Our analysis reveals that zoning in Europe is overwhelmingly focused on wood production, while there has been little concomitant protection of forests in strict reserves. Moreover, most strict forest reserves are

The serotonin receptor 3E variant is a risk factor for female IBS-D - Nikola Fritz; Sabrina Berens; Yuanjun Dong; Cristina Martínez; Stefanie Schmitteckert; Lesley A. Houghton; Miriam Goebel-Stengel; Verena Wahl; Maria Kabisch; Dorothea Götze; Mauro D’Amato; Tenghao Zheng; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT 3 receptor family. 5-HT 3 Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT 3 R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients ( p = 0.0187); more specifically, in those diagnosed with IBS-D ( p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.

Pharmacogenetic association of diabetes-associated genetic risk score with rapid progression of coronary artery calcification following treatment with HMG-CoA-reductase inhibitors —results of the Heinz Nixdorf Recall Study - Sonali Pechlivanis; Dominik Jung; Susanne Moebus; Nils Lehmann; Amir A. Mahabadi; Per Hoffmann; Raimund Erbel; Markus M. Nöthen; Hagen S. Bachmann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
HMG-CoA-Reductase inhibitors (HMGRIs) are currently the most widely used group of drugs in patients with coronary artery disease (CAD) and are given preemptively to patients with high levels of cholesterol, including those with diabetes mellitus (DM). However, intake of HMGRIs also increases the progression of coronary artery calcification (CAC) and the risk of developing DM. This study aimed to investigate whether HMGRI intake interacts with the diabetes-associated genetic risk score (GRS) to affect CAC progression using data from the population-based Heinz Nixdorf Recall (HNR) study. CAC was measured in 3157 participants using electron-beam computed tomography twice, at baseline (CAC b ) and 5 years later (CAC 5y ). CAC progression was classified as slow, expected, or rapid based on predicted values. Weighted DM GRS was constructed using 100 diabetes mellitus–associated single nucleotide polymorphisms (SNPs). We used log-linear regression to evaluate the interaction of HMGRI intake with diabetes-associated GRS and individual SNPs on CAC progression (rapid vs. expected/slow), adjusting for age, sex, and log(CAC b + 1). The prevalence of rapid CAC progression in the HNR study was 19.6%. We did not observe any association of the weighted diabetes mellitus GRS with the rapid progression of CAC (relative risk (RR) [95% confidence interval (95% CI)]: 1.01 [0.94; 1.10]). Furthermore, no indication of an interaction between GRS and HMGRI intake was observed (1.08 [0.83; 1.41]). Our analyses showed no indication that the impact of HMGRIs on CAC progression is significantly more severe in patients with a high genetic risk of developing DM than in those with a low GRS.

Exome sequencing identifies potential novel candidate genes in patients with unexplained colorectal adenomatous polyposis - Isabel Spier; Martin Kerick; Dmitriy Drichel; Sukanya Horpaopan; Janine Altmüller; Andreas Laner; Stefanie Holzapfel; Sophia Peters; Ronja Adam; Bixiao Zhao; Tim Becker; Richard P. Lifton; et al. (Familial Cancer, 2016)

From Fish to Jellyfish in the Eutrophicated Limfjorden (Denmark) - Hans Ulrik Riisgård; Per Andersen; Erik Hoffmann (Estuaries and Coasts, 2012)

Remote sensing and GIS in hydrogeology - Jörn Hoffmann; Per Sander (Hydrogeology Journal, 2007)

The stabilisation of wet sediment cores by means of a polyethylene glycol/freeze-drying treatment for display and permanent storage - Per Hoffmann; Jürgen Pätzold (Geo-Marine Letters, 2001)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)